2022
DOI: 10.1002/1878-0261.13214
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and post‐treatment blood‐based genomic landscape of patients with ROS1 or NTRK fusion‐positive solid tumours treated with entrectinib

Abstract: Genomic tumour profiling informs targeted treatment options. Entrectinib is a tyrosine kinase inhibitor with efficacy in NTRK fusion‐positive (‐fp) solid tumours and ROS1‐fp non‐small cell lung cancer. FoundationOne® Liquid CDx (F1L CDx), a non‐invasive in vitro next‐generation sequencing (NGS)‐based diagnostic, detects genomic alterations in plasma circulating tumour DNA (ctDNA). We evaluated the clinical validity of F1L CDx as an aid in identifying patients with NTRK‐fp or ROS1‐fp tumours and assessed the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In an analysis of TKI–naïve patients from the STARTRK-2 study (data cutoff: May 2018), 26% (n = 5 out of 19) of patients had detectable acquired mutations in ROS1 ( ROS1 G2032R ; ROS1 F2004C/I ) at PD after treatment with entrectinib. 27 Although no known ROS 1 -acquired resistance mutations were identified in our study (analysis in the post-crizotinib cohort), other still unidentified mechanisms, such as epigenetic changes, may be involved. In addition, our molecular analysis was carried out on circulating tumor DNA, which may have limitations compared with the sequencing of tumor tissue.…”
Section: Discussionmentioning
confidence: 64%
“…In an analysis of TKI–naïve patients from the STARTRK-2 study (data cutoff: May 2018), 26% (n = 5 out of 19) of patients had detectable acquired mutations in ROS1 ( ROS1 G2032R ; ROS1 F2004C/I ) at PD after treatment with entrectinib. 27 Although no known ROS 1 -acquired resistance mutations were identified in our study (analysis in the post-crizotinib cohort), other still unidentified mechanisms, such as epigenetic changes, may be involved. In addition, our molecular analysis was carried out on circulating tumor DNA, which may have limitations compared with the sequencing of tumor tissue.…”
Section: Discussionmentioning
confidence: 64%
“…To gain a better understanding of the prevalence of MET amplification as a mechanism of resistance to entrectinib in ROS1+ NSCLC, we evaluated circulating tumor DNA (ctDNA) of ROS1+ STARTRK‐2 trial participants. 45 Of 105 ROS1+ NSCLC patients with successfully sequenced ctDNA both at study enrollment and at progression on entrectinib, 2 (1.9%) samples displayed CNA of MET via FoundationOne Liquid CDx. Of these two patients, one patient had no detectible CNA at study enrollment but displayed MET amplification by day 166 of entrectinib therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, the FoundationOne Liquid CDx test was evaluated for its clinical validity for the identification of patients with NTRK or ROS1 fusions that may benefit from treatment with entrectinib (Rozlytrek, Roche Pharma) or those with acquired resistance to TKIs. It was found that plasma testing can be used as a complement to tissue genotyping for clinical decisions [ 221 ]. Another larger study in a pan-cancer patient population (36,916 ctDNA samples and 368,931 tumor tissue samples) confirmed that ctDNA analysis could reliably identify oncogenic fusions with high concordance to tissue genotyping results [ 222 ].…”
Section: Liquid Biopsy Testing In Nsclcmentioning
confidence: 99%